Peranan Sekuens Dixon Pada Pemeriksaan Mri Wrist Joint Tanpa Kontras Kasus Intraosseus Hemangioma - Zenitha Azzahra, Rafa; I Made Lana Prasetya; Nadra (Pusat riset dan Inovasi Nasional, 2023)
Magnetic Resonance Imaging (MRI) is a medical diagnostic imaging technique that works on the principle of nuclear magnetic resonance. MRI aircraft can produce internal diagnostic images of human needs both in sagittal, coronal, and transverse cuts by not using ionizing radiation (X-rays) and also not using radioactive substances but based on the principle of magnetic resonance of hydrogen atomic nuclei to reveal anatomically and pathologically to establish clinical diagnoses, one of which is Intraosseus hemangioma in the wrist joint. Intraosseous hemangioma is classified as a benign tumor of a vascular nature. The use of dixon sequences is proposed for the assessment of the water content of metaphysical bone marrow, with a short scan time. Dixon sequence imaging can be used for suppression of fat in the extremities, but also for quantification of fat in bones. The research method used is descriptive research with an observational approach. Data collection was carried out from November 7, 2022 to February 7, 2023 using a 3 Tesla Mri Siemens Magnetom Vida aircraft. The patient sample used in this study was a patient with complaints of the wrist joint. Data collection is carried out through observation, interviews and documentation Wrist Joint Examination in Intraosseus Hemangioma Cases using Siemens Magnetom Vida 3 Tesla MRI aircraft has an examination procedure with sequence designs Localizer_tra, Localizer_sag + cor+tra, t1_tse_tra_2mm, t2_tse_dixon_fs_cor_2mm, t2_tse_dixon_fs_sag_2mm , t1_vibe_wo_cor_ iso,Pd_tse_fs_tra_2, 5_mm